EVALUATING PARTICIPANTS’ UNDERSTANDING OF TEXT-TO-DESIGN FOR LOCAL-BASED WISDOM: EVALUASI PEMAHAMAN PESERTA PADA APLIKASI TEXT-TO-DESIGN BERBASIS KEARIFAN LOKAL - Cendra Devayana Putra; Daniel Evan Rusli; I Kadek Dwi Nuryana; Rahadian Bisma (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: This study presents an evaluation of the dissemination of the Text-to-Design (TTD) application for developing design materials based on local wisdom. Objective: With increased accessibility to AI-supported technology, educators can apply TTD tools to produce learning materials that are consistent, flexible, and culturally contextual. Method: Using survey data and participant feedback, the study analyzes levels of understanding, clarity of presentation, the usefulness of practical sessions, and development recommendations. Results: The findings indicate a high level of understanding (88.9%), strong engagement through hands-on activities, and interest in integrating local content into digital listening materials. Conclusion: These results align with recent research on digital literacy and culturally relevant learning.